THROMBOPHLEBITIS OF PREPUBIC VEINS IN PATIENTS WITH APLASIA OF THE LEFT COMMON AND LEFT EXTERNAL ILIAC VEINS-CASE REPORT - Crnokrak Bogdan; Zdravkovic Darko; Toskovic Borislav; Colakovic Natasa (Sanamed, 2020)
Introduction: A congenital defect of some of the large veins that drain blood from the lower extremity is a very rare occurrence and, considering the clinical consequences, it is generally diagnosed at a relatively early age - in childhood or youth. Within the complex classification of vascular malformations, a special category is comprised of large blood vessel malformations, also called truncal vascular malformations. In comparison to other anomalies, aplasia or lack of development of a certain segment in the deep venous systems, potentially has the most serious hemodynamic consequences. The appearance of varicose veins, through which the venous blood is drained distally to the obstruction into an unusual area, such as the lower part of the trunk or the anterior abdominal wall, usually spurs the patient into action in terms of conducting diagnostic procedures so that diagnosis can be reached before complications occur. Defects of large magistral deep veins, which remain unrecognized until adulthood and which are diagnosed after complications in the drainage venous network occur, are infrequent. Complications that can arise in association with this malformation are manifested not only in varicosally altered collateral veins, but also in the venous drainage area distal to the obstruction.